Sociological survey amongst practitioners: A decisional tool for sports organizations? The case of the French Federation of Karate and Associated Disciplines. Issue 2 (3rd May 2016) - Fuchs, Julien; Guyon, Frédérick
Abstract : Karate is practiced in France today in a great number of forms by about 230, 000 practitioners affiliated with the French Federation of Karate and Associated Disciplines. There are multiple modalities according to which karatekas perceive their activity. A sociological survey commissioned by the French Federation and financed almost entirely by the Ministry of Health, Youth, Sports and Community Life was carried out between 2008 and 2010 in an attempt to highlight the typical profile of the practitioners. This article shows that the implementation of the sociological survey testifies to the Federation's desire to take into account the expectations of its members, and thus, to assume a social role. However, in a context marked by the eagerness of the sports institutions to set their action within the high-level, performance model, this endeavor has met with serious difficulties, not least within the Federation itself, for which the survey seems to have served more as a pretext than a genuine piloting tool.